Sympathovagal Imbalance in Prehypertensive Offspring of Two Parents versus One Parent Hypertensive - G. K. Pal; Pravati Pal; Nivedita Nanda; V. Lalitha; T. K. Dutta; C. Adithan (International Journal of Hypertension)
Objective. Though prehypertension has strong familial predisposition, difference in pathophysiological mechanisms in its genesis in offspring of both parents and single parent hypertensive have not been elucidated. Methods. Body mass index (BMI), waist-hip ratio (WHR), basal heart rate (BHR), blood pressure (BP), HR and BP response to standing, deep breathing difference, BP response to handgrip and spectral indices of heart rate variability (HRV) were analyzed in normotensive offspring of two parents hypertensive (Group I), normotensive offspring of one parent hypertensive (Group II), prehypertensive offspring of two parents hypertensive (Group III) and prehypertensive offspring of one parent hypertensive (Group IV). Results. Sympathovagal imbalance (SVI) in prehypertensive offspring was observed due to increased sympathetic and decreased vagal activity. In group III, SVI was more prominent with greater contribution by vagal withdrawal. LF-HF ratio, the marker of SVI was correlated more with diastolic pressure, 30 : 15 ratio and E : I ratio in prehypertensives and the degree of correlation was more in group III prehypertensives. Conclusion. Vagal withdrawal plays a critical role in development of SVI in prehypertensive offspring of hypertensive parents. The intensity of SVI was more in offspring of two parents hypertensive compared to single parent hypertensive.